Development and Acceptability of Gamified Supplementary Materials in Mathematics for Grade One Pupils - Rubaya, Marjoreen (International Journal of Sustainability and Advanced Integrated Research, 2026)
The study aimed to develop and determine the acceptability of gamified supplementary materials in Mathematics for Grade One pupils in selected public elementary schools in Cainta District, Schools Division Office of Rizal, during the School Year 2025-2026. Participating schools included Cainta Elementary School, Marick Elementary School, Karangalan Elementary School, Saint Anthony Elementary School, and St. Joseph Elementary School. The total population of primary grade teachers in these schools served as respondents to evaluate the developed materials. Respondents were described based on age, sex, civil status, educational attainment, position title, length of service, and in-service trainings attended.A descriptive evaluative research design, combining qualitative and quantitative methods, was employed. Data were gathered using a researcher-made questionnaire to assess the level of acceptability of the gamified materials with respect to objectives, contents, language and style, usefulness, and user-friendliness.Findings indicated that most teacher-respondents were 31 years old and above, female, married, and pursuing graduate studies, with position titles of Teacher I or Teacher II. The majority had more than ten years of service and had attended seminars and trainings ranging from division to international levels. Evaluations revealed that the developed gamified supplementary materials were “very much acceptable” in terms of language and style and “much acceptable” in terms of objectives, contents, usefulness, and user-friendliness. No significant differences were observed in evaluations based on respondents’ demographic and professional profiles.The study concluded that the gamified supplementary materials in Mathematics are highly acceptable across all evaluated aspects and are independent of teachers’ personal and professional characteristics. It is recommended that teachers continue to utilize these materials to enhance Grade One pupils’ mathematical competencies. Further development of gamified materials across other subjects is encouraged to enrich teaching strategies and improve learners’ engagement. Additional studies may explore the effectiveness of gamified materials in improving learning outcomes..